Penanganan Sinkop (Pingsan) Akibat Aktivitas Olahraga: Studi Observasi dan Wawancara di Puskesmas Boba, Ngada - Yolenta Klarina Ewinda Dhei; Claudius Novan; Robertus Lili Bile (STIKes Ibnu Sina Ajibarang, 2026)
Syncope or fainting is an emergency condition that commonly occurs during sports activities due to reduced blood flow and oxygen to the brain. Rapid and appropriate management is essential to prevent further complications. This study aims to determine the syncope management procedures following sports activities performed by healthcare professionals at primary healthcare facilities. This study employed direct observation and structured interviews with healthcare workers at Puskesmas Boba, Ngada on November 28, 2025. Observed aspects included initial patient condition, initial actions, vital signs examination, medical assistance provision, condition monitoring, and follow-up actions. Healthcare workers performed management according to first aid procedures by positioning patients supine, elevating both legs, loosening tight clothing, checking vital signs using sphygmomanometer and stethoscope, providing oxygen and fluids when necessary, and monitoring until condition stabilized. Main causative factors of syncope were dehydration, physical fatigue, hypoglycemia, and anemia. Syncope management requires systematic actions and adequate medical equipment. Preventive education for athletes and the community, as well as collaboration among healthcare workers, coaches, and physical education teachers is crucial to prevent recurrence.